THE LEVEL OF IMPLEMENTATION OF CATTLE FARM BIOSECURITY SYSTEM RELATED TO PREVENTION OF FOOT AND MOUTH DISEASE IN GIANYAR REGENCY OF BALI - Jazuli Azra Mr; I Ketut Suada; Romy Muhammad Dary Mufa (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Foot Foot and Mouth Disease is one of the acute diseases, this disease is caused by a virus of the genus Aphtovirus. This virus attacks cloven-hoofed animals both livestock and wild animals, the spread rate of FMD virus is very high, the mortality rate of this virus is 20% in young animals and 2% in adult animals. To prevent this disease itself, in addition to vaccination, it is necessary to apply biosecurity. The purpose of this study is to determine the level of application of biosecurity system in cattle farms, for the sample used in this study are simantri cattle farms and cattle groups (non-simantri) in Gianyar Regency. This research was conducted with interview techniques to simantri cattle farmers and cattle groups (non-simantri) in Gianyar Regency using a questionnaire. The results of the research previously tabulated into Microsoft Excel and analyzed descriptively qualitative shows that the level of application of biosecurity system on cattle farms in Gianyar regency is categorized into the category of sufficient. This shows that the application of biosecurity on cattle farms in Gianyar Regency has not been implemented properly. Based on the research results obtained, there are several suggestions given by the author, as follows: Although the spread of foot and mouth disease in Gianyar Regency has decreased, farmers are expected to always pay attention to the sanitation of cages and the cleanliness of their livestock, because poor sanitation is a source of disease, Traffic supervision or traffic control must also be considered by farmers, because this component is a very large factor in the spread of a pathogen, things that need to be considered are: As an effort to prevent the re-entry of foot and mouth disease (FMD) in cattle farms owned by farmers in Gianyar Regency, it is hoped that farmers can improve the biosecurity system on their farms. Where biosecurity is the main guard in protecting livestock from the spread of disease-causing microorganisms.